Hubungan Gratitude dengan Body Dissatisfaction pada Perempuan Emerging Adulthood Pengguna Instagram - Raki’ah, Raki’ah; Yasmin, Maya (Indo-MathEdu Intellectuals Journal, 2024)
This study aims to examine the relationship between gratitude and body dissatisfaction in emerging adulthood women Instagram users. The type of research used is correlational quantitative research The number of research samples is 385 emerging adulthood women Instagram users domiciled in West Sumatra with sampling carried out through accidental sampling techniques. The measuring tools used are the gratitude scale and the body dissatisfaction scale. The analysis used was pearson correlation. Based on the results of the study, a correlation value of -0.385 and p < 0.05 was obtained, this shows that there is a negative relationship between gratitude and body dissatisfaction in emerging adulthood women Instagram users